Implementasi gerakan omnidirectional pada robot rugby - Agus Siswoyo; Eko Arianto (J-Innovation, 2022)
Robots in the KRAI competition (Indonesian ABU Robot Contest) are required to be able to maneuver and move well, efficiently and quickly in order to be able to carry out the task of picking up and kicking rugby balls. In order for the robot to move quickly and precisely, a wheel that can move dynamically is needed. The wheel used is the Omniwheel. This wheel has a small wheel located on the outer side of the main wheel, so that the movement of the rugby robot can run smoother when changing positions. With dynamic and efficient maneuvers and displacement of the rugby robot, the robot can move more agile and can stop in the desired position.